2013
DOI: 10.1088/0953-8984/25/22/225004
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion: role of bulk viscoelasticity and surface roughness

Abstract: We study the adhesion between smooth polydimethylsiloxane (PDMS) rubber balls and smooth and rough poly(methyl methacrylate) (PMMA) surfaces, and between smooth silicon nitride balls and smooth PDMS surfaces. From the measured viscoelastic modulus of the PDMS rubber we calculate the viscoelastic contribution to the crack-opening propagation energy γeff(v,T) for a wide range of crack tip velocities v and for several temperatures T. The Johnson-Kendall-Roberts (JKR) contact mechanics theory is used to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 48 publications
2
78
0
Order By: Relevance
“…After the loading process completed, the unloading process was performed until the lens detached. A dependence of the maximum loading displacement on the adhesion hysteresis has been reported [16,20]. Hence, three different maximum loading displacement were chosen: −Z max = 10, 20, 30 μm, which is sufficiently smaller than the thickness of the PDMS block 10 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the loading process completed, the unloading process was performed until the lens detached. A dependence of the maximum loading displacement on the adhesion hysteresis has been reported [16,20]. Hence, three different maximum loading displacement were chosen: −Z max = 10, 20, 30 μm, which is sufficiently smaller than the thickness of the PDMS block 10 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The energy dissipation in the adhesive contact is mainly investigated and discussed using the strain energy release rate G (i.e., the energy required to separate unit contact area J/m 2 ) [9][10][11][12][13][14][15][16][17][18]. Maugis and Barquins [10] first introduced a concept of linear elastic fracture mechanics into the Johnson-Kendall-Roberts (JKR) contact [6].…”
mentioning
confidence: 99%
“…[26]). However, it is also observed that contamination of the surfaces by dust particles (or roughening) can significantly reduce w 0 [18]. As a parallel to these semi-empirical models, we take…”
Section: Peeling Models (A) Viscoelastic Fracturementioning
confidence: 99%
“…From simple tests based on the gravitational deflection of a section of the rubber clamped horizontally at one end, we estimated that L b = (B/ρgd) 1 For many surfaces, the work of adhesion w 0 (or w ± ) is quoted to be of the order of 0.1 J m −2 . Estimates of the parameters (n, U F ) in the fit (4.3) are more varied: data for a PDMS surface in contact with glass or acrylic suggest a range from (0.4, 10 −6 m s −1 ) to (0.12, 10 −9 m s −1 ) [18,22]. Data from Gent [35], Maugis & Barquins [21] and Shull [13] indicate that (n, U F ) ∼ (0.25, 10 −12 m s −1 ) for a styrene butadiene rubber, (0.6, 10 −6 m s −1 ) for polyurethane, and (0.6, 10 −8 m s −1 ) for PNBA, respectively.…”
Section: Appendix a Physical Parameter Estimatesmentioning
confidence: 99%
See 1 more Smart Citation